Based on the Analysis of Yanghe Liquors SCP - Li, Zongmin (Journal of Global Economy, Business and Finance, 2025)
The liquor industry, as a traditional sector in China, has a long history. Suqian City, known as the "Capital of Liquor," is also a pillar industry for its liquor sector. Through brand marketing and technological innovation, Suqian Yanghe Liquor has achieved rapid growth in a short period. In response to the current market development status of the liquor industry, this study analyzes the market structure, behavior, and performance of Suqians liquor market using the SCP paradigm. It finds that the overall market concentration of Suqians liquor industry is relatively low. By exploring the current state of Suqians liquor industry and proposing countermeasures, it suggests: enhancing brand marketing to boost brand influence; strengthening talent cultivation to enhance innovation momentum; controlling product quality to improve the industrial chain; identifying consumer groups to broaden sales markets.